Perpendicularly Magnetized MnxGa‐Based Magnetic Tunnel Junctions: Materials, Mechanisms, Performances, and Potential Applications - Xupeng Zhao; Jianhua Zhao (Advanced Materials Interfaces, 2022)
Abstract Magnetic tunnel junctions (MTJs) exhibit a great profusion of unique functional properties, such as nonvolatility, scalability, high endurance, and low power consumption. For this reason, they have been widely investigated in spin‐based logic and memory devices. Compared with conventional in‐plane MTJs, perpendicular MTJs (pMTJs) enable lower critical switching current and higher integration density. So far, CoFeB/MgO structures with interface‐induced perpendicular magnetic anisotropy (PMA) are the most common ferromagnetic (FM) electrodes in pMTJs, whereas their relatively weak interfacial PMA restricts further development of device nodes. In the past decade, perpendicularly magnetized MnxGa binary alloys, including FM L10‐MnGa and ferrimagnetic D022‐Mn3Ga, have drawn intense attention for serving as a promising magnetic electrode in various MTJ stacking structures because of their large PMA, high spin polarization, and small magnetic damping constant. From an application perspective, MTJs with ultrathin MnxGa electrode show merits in developing high‐density magnetic memory, high‐frequency spin‐torque oscillators, and tunneling magnetoresistance effect‐based high‐field sensors. Herein, the aim is to provide a comprehensive review of recent progress in perpendicularly magnetized MnxGa‐based MTJs. The conclusions and future prospects are also given to inspire more in‐depth research and advance the practical applications.